Balancing capacitor voltage in three-level NPC converter - Nguyen , Minh Tâm; Do , Đức Trí; Hua , Duy Tiến; Truong , Thị Bích Ngà (Journal of Technical Education Science, 2016)
This paper presents a solutionfor balancing capacitor voltage of a three-level NPC inverter by controlling DC-link in capacitors. When the capacitor’s voltage varies, it should be stabilized at zero in order to not create imbalance in the system. The imbalance of capacitor’s voltage will cause unexpected lower harmonic. On the other hand, when capacitor’s voltage was balanced, the center source phase DC voltage will be better than when the inverter configuration works in imbalance mode. This paper uses the method that firstly checking current direction on the power line in the capacitor, then accordingly controlling switches for capacitor voltage balance. Simulation and experimental results are provided in order to validate the proposed method.